Pengembangan Aplikasi Game Edukasi dalam Membentuk Karakter anak - Yenti Juniarti (Widya Wacana: Jurnal Ilmiah, 2021)
The purpose of this study was to develop educational game applications in shaping children's character at Damhil Kindergarten. This study uses development research (R & D) with the Borg & Gall approach. The subjects of this study were parents of students and children totaling 35 people. Based on the results of the needs analysis that 100% of parents have played, 50% of children have smartphones, 100% agree with the development of educational games in bringing out children's characters. While the results of the small group trial were 74.08% valid and in the large group trials 86.06% were valid. Based on the results obtained, children's characters can be formed through educational games, which in these games have the characters of honesty, discipline, responsibility, respect for people and politeness. Of course this educational game does not only stimulate children's character but is able to develop five aspects of development, such as religious and moral values, cognitive, language, social, emotional and physical motor skills. Through this educational game character, children are able to implement good activities contained in the KIBAS educational game (Tsakib and Arash). Keywords: Educational Games, Characters; Child ABSTRAK Tujuan dari penelitian ini untuk mengembangkan aplikasi game edukasi dalam membentuk karakter anak pada sekolah taman kanak-kanak Damhil. Penelitian ini menggunakan penelitian pengembangan (R & D) dengan pendekatan Borg & Gall. Subjek penelitian ini adalah orangtua murid dan anak berjumlah 35 orang. Berdasarkan hasil analisis kebutuhan bahwa 100% orangtua pernah melakukan bermain, 50% anak-anak memiliki smartphone, 100% setuju dengan pengembangan game edukasi dalam memunculkan karakter anak. Sedangkan hasil uji coba kelompok kecil yaitu 74.08% valid dan pada uji coba kelompok besar 86.06% valid. Berdasarkan hasil yang di dapat bahwa Karakter anak bisa di bentuk melalui game edukasi, yang mana pada game tersebut memiliki karakter jujur, disiplin, tanggung jawab, menghargai orang dan sopan santun. Tentu game edukasi ini tidak hanya merangsang karakter anak melainkan mampu mengembangkan lima aspek perkembangan, seperti nilai agama dan moral, kognitif, bahasa, sosial emosional dan fisik motorik. Melalui karakter game edukasi ini anak mampu menerapkan aktivitas yang baik yang terdapat di dalam game edukasi KIBAS (Tsakib dan Arash) Kata kunci: Game Edukasi, Karakter; Anak